LOYALITAS KONSUMEN GORIDE DI KOTA SEMARANG - Ikasari, Hertiana; Mahardhika, Fawwaz Shele (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2021)
Consumer loyalty is an indication of the performance appraisal of the management of a company or business actor. This also applies to business actors who use internet technology as their marketing base. The proliferation of businesses that use the internet as a marketing method has also penetrated the transportation business. One of these online transportation service companies is Gojek, where GoRide is one type of service. The problem faced by GoRide is that there are several complaints from consumers that must be considered because it will affect the sustainability of using the product and of course it becomes a tendency for customers to be loyal to a certain object. The purpose of this study was to analyze the effect of the variables of trust, consumer satisfaction and promotion on GoRide consumer loyalty in Semarang municipality. The sampling technique used purposive sampling method. The analytical tool used is multiple linear regression. The results obtained are the variables of trust, customer satisfaction and promotion have a positive and significant effect on consumer loyalty GoRide in Semarang Municipality.